COBERTURA VACINAL ENTRE CASOS CONFIRMADOS DE DOENÇAS IMUNOPREVENÍVEIS DE NOTIFICAÇÃO COMPULSÓRIA EM MATO GROSSO DO SUL, 2011 A 2020 - DANIELLI DE ALMEIDA MOURA (2023)
The National Immunization Program of Brazil has been distributed millions of doses of vaccines, universally and free of charge. However, in recent years a reemergence of already controlled diseases has been observed, which can be attributed to the significant drop in vaccination coverage throughout the country. Since the 1990s, childhood vaccine coverages (VC) were above 95%; however, as of 2016, these coverages have declined expressively, which warns of emerging health crises. Given this scenario, this study objective was to estimate the VC in the population of individuals who were notified as confirmed cases of immunopreventable diseases of compulsory notification, whose vaccines are available at the PNI, in Mato Grosso do Sul, from 2011 to 2020. This is a descriptive cross-sectional study based on data from the National System of Disease Notification (SINAN). A descriptive analysis of the results was conducted. Incidence was used as a measure of disease frequency and the proportion of vaccinated among all cases was used to describe VC by disease and sex group. From January 2011 to December 2020, 34822 cases of vaccine-preventable diseases were reported to SINAN of Mato Grosso do Sul, of these, 17595 (50.53%) consisted of confirmed cases. The highest CV among the confirmed cases of each disease, was 50% for diphtheria, followed by pertussis (48.93%), rabies (33.33%), tetanus (26.66%), hepatitis B (26.57%), influenza (13,49%), varicella (13.09%), hepatitis A (6.58%) and Haemoplhilus meningitis (0). The median CV among confirmed cases of these diseases, except varicella, remained extremely low over the ten years of study, ranging from 18.83% in the year 2012 to 39.21% in 2013. From 2013 to 2015, there was a 48.83% drop in mean CV among confirmed cases of these eight immuno-preventable diseases; from 2017 to 2018, the drop was almost 45.46%. In Mato Grosso do Sul, considering coverage data for the general population that are in the public domain at DATASUS, from 2011 to 2020, we observed a downward trend in vaccine coverage, which reached percentages above 95% between the years 2014 and 2015, declining to 64% in 2016. On the other hand, considering only the vaccination data among the confirmed cases of diseases preventable by immunization, the vaccination coverage is drastically lower, since our data evidenced a total of 22.01% CV among the confirmed cases of nine vaccine-preventable diseases, whose vaccines are available at SUS. Keywords: vaccination, vaccination coverage, immuno-preventable diseases, compulsory notification, epidemiology.